Execution of Advertising and Celebrity Endorsement - Peter Mikuláš,; Jaroslav Světlík,, (Communication Today, 2025)
The article focuses on the topic of celebrity endorsement in TV commercials in terms of their perception by Generation Y. For the purposes of the study effectiveness of advertising was reduced on recall of commercials – in the sense of one’s ability to correctly link the celebrity to promoted brand/product. The aim of the text is to verify the effectiveness of celebrity endorsement concepts both on the basis of particular attributes and qualities of the endorser and on the execution of commercials. This approach allows operative assessment of validity of some established theories regarding the celebrity endorsement. In the pre-research phase we applied a hybrid post-testing methodology, namely the recall method, to select two groups of celebrity endorsers: successful and unsuccessful ones. In the following research we employed a method of polarity profile on selected celebrity endorsers, while five adjective groups were chosen. These groups represented the examined dimensions of attractiveness, credibility, expertise, and the attitude towards the advertisement. Results of the study confirm little evidence which would support ability to recall linkage of the celebrity with the promoted product/brand. However, the research approves presence of some irritating elements related to the perception of commercials, which were identified as applicable to effective celebrity endorsement. These findings emphasise the relevance of proper execution of commercials which, in the context of celebrity endorsement, could be thought of as a relatively marginalised issue.